Pelatihan Penerapan Metode Plans untuk Mengembangkan Efikasi Diri dalam Pengambilan Keputusan Karier Siswa di Kabupaten Purwakarta - Fatimah, Siti; Suherman, Maya Masyita; Rohaeti, Euis Eti (Jurusan Bimbingan dan Konseling Islam, 2019)
The general objective in the implementation plan of community service is to socialize a way or method to develop students' self-efficacy in career decision making in Purwakarta. The type of outcomes generated from this training is to increase teacher competency in developing self-efficacy of student career decisions. Based on the interview results it was found that many teachers did not understand how to provide assistance to students in the career field, so that it was more burdened / directed to the guidance and counseling teacher in the school. However, because of the very far ratio between teacher guidance and counseling with students, so many students do not get career guidance services that impact on career decision-making of students who are made carelessly and part of it (conformity in career).